Innovation research in value chains - Kabi, Fred; Ssebuliba, James M.; Mugisha, Jonny; Namuwoza, Charity; Høgh Jensen, Henning (ICROFS news, 2011)
In large parts of the Sub-Saharan sub-continent, smallholder agricultural production and food security has remained consistently low1. Natural resource management is in distress and most rural Africans remain poor and food insecure despite widespread macroeconomic, political and sector reforms. Most predictions are that these Africans will remain food insecure in the foreseeable future2. In this article, the authors present the novel ProGrOV project.
Keywords: Innovation research; Value chains